Global Geriatric Assessment and In-Hospital Bleeding Risk in Elderly Patients with Acute Coronary Syndromes: Insights from the LONGEVO-SCA Registry - Ariza-Solé, Albert; Guerrero, Carme; Formiga, Francesc; Aboal, Jaime; Abu-Assi, Emad; Marín, Francisco; Bueno, Héctor; Alegre, Oriol; López-Palop, Ramón; Vidán, María T.; Martínez-Sellés, Manuel; Díez-Villanueva, Pablo; Vilardell, Pau; Sionis, Alessandro; Vives-Borrás, Miquel; Sanchís, Juan; Bañeras, Jordi; Rafecas, Agnès; Llibre, Cinta; López, Javier; González-Salvado, Violeta; Cequier, Àngel (Thrombosis and Haemostasis, 2018)
Background Bleeding risk scores have shown a limited predictive ability in elderly patients with acute coronary syndromes (ACS). No study explored the role of a comprehensive geriatric assessment to predict in-hospital bleeding in this clinical setting.Methods The prospective multicentre LONGEVO-SCA registry included 532 unselected patients with non-ST segment elevation ACS (NSTEACS) aged 80 years or older. Comorbidity (Charlson index), frailty (FRAIL scale), disability (Barthel index and Lawton–Brody index), cognitive status (Pfeiffer test) and nutritional risk (mini nutritional assessment-short form test) were assessed during hospitalization. CRUSADE score was prospectively calculated for each patient. In-hospital major bleeding was defined by the CRUSADE classification. The association between geriatric syndromes and in-hospital major bleeding was assessed by logistic regression method and the area under the receiver operating characteristic curves (AUC).Results Mean age was 84.3 years (SD 4.1), 61.7% male. Most patients had increased troponin levels (84%). Mean CRUSADE bleeding score was 41 (SD 13). A total of 416 patients (78%) underwent an invasive strategy, and major bleeding was observed in 37 cases (7%). The ability of the CRUSADE score for predicting major bleeding was modest (AUC 0.64). From all aging-related variables, only comorbidity (Charlson index) was independently associated with major bleeding (per point, odds ratio: 1.23, p = 0.021). The addition of comorbidity to CRUSADE score slightly improved the ability for predicting major bleeding (AUC: 0.68).Conclusion Comorbidity was associated with major bleeding in very elderly patients with NSTEACS. The contribution of frailty, disability or nutritional risk for predicting in-hospital major bleeding was marginal.
Keywords: elderly; bleeding; comorbidity; acute coronary syndromes; frailty